FROM ARCHAIC MYTH TO SIMULACRUM: THE CONTRADICTIONS BASED ON COMMUNITY - Топалова, С.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This article examines specific transformation mythological component within different forms of mass political consciousness. According to the criteria defined by the author of the comparative analysis of archaic myth, ideology, modern political myth and simulacrum. Identified traits are genetically inherited ideological myth of the archaic, and also determined the main differences of modern political myths and simulacra.